Penerapan Teknik Mobilisasi Dini terhadap Penurunan Skala Nyeri pada Pasien Post Sectio Caesarea RSUD Dr. Moewardi Surakarta - Mita Putri Sugiyanto; Anjar Nurrohmah; Alfida Fitri Hapsari (Jurnal Medika Nusantara, 2023)
Background: Sectio caesarea is an effort to deliver with a surgical procedure through the technique of making incisions in the abdominal wall and uterus to remove babies with a fetus weighing more than 1000 grams or gestational age > 28 weeks Niklasson, (2020). The current trend of sectio caesarean (SC) deliveries is not only for emergencies. The trend of deliveries by caesarean section has led to an increase in caesarean sections in a number of hospitals, both in private hospitals and government hospitals. Ayuningtyas et al., (2020). Purpose: To find out the results of the implementation of whether there is a decrease in pain intensity in post sectio caesarea patients by providing early mobilization techniques at RSUD Dr. Moewardi Surakarta. Methods: Using a case study design, the subject was 1 post Sectio Caesarea mother who was treated in the ponek room of RSUD Dr. Moewardi Surakarta. Measuring instrument for the level of pain using the Numeric Rate Score (NRS) pain scale. The application is carried out for 3 consecutive days, 1 day is done once with a duration of 15 minutes. Findings: before the implementation of early mobilization exercises on pain scale 6 respondents was included in the moderate pain category, whereas after the implementation of early mobilization exercises on pain scale 2 respondents included in the mild pain category. Implication: Application of early mobilization techniques to mothers after 6-8 hours after Sectio Caesarea there was a decrease in pain scale after being given early mobilization therapy in post sectio caesarea patients at RSUD Dr. Moewardi Surakarta